PERSEPSI MAHASISWA AKUNTANSI DAN AKUNTAN PENDIDIK TERHADAP KOMPETENSI YANG DIBUTUHKAN LULUSAN AKUNTANSI - Tri Riczqi Srihadi Putri; Puji Harto (Diponegoro Journal of Accounting, 2012)
This study investigates what competencies accounting students and accounting academics perceive have been developed during an undergraduate course, and compare this to competencies that they believe need for career success. The questionnaire in this study is a questionnaire that has been used previously by Kavanagh (2008), which was adapted from Albrecht and Sack (2000). The questionnaire used was tested validity and reliability. The method of analysis used is paired sample t-test. The results showed that there is a large discrepancy between the two.